Market Structure, Conduct, and Performance in Indonesia's Cellular Telecom Industry - Fikri, Muhammad Kanzul; Firmansyah (Universitas Negeri Semarang, 2024)
This research investigates the factors that impact the performance of the Indonesian mobile telecommunications sector by employing two predominant theoretical frameworks: the Harvard School (market power hypothesis) and the Chicago School (efficiency structure hypothesis). The methodology encompasses descriptive analysis to scrutinize the Structure-Conduct-Performance (SCP) model, data envelopment analysis (DEA) to assess technical and scale efficiencies, and panel data regression to determine the influences on company performance. The data derive from annual reports of mobile telecommunications entities spanning 2010 to 2022. Findings indicate the presence of market power within the industry, highlighted by the existence of five major operators and a notable concentration ratio. Further, the analysis of advertising and welfare expenses demonstrates significant investments in advertising to secure and expand market presence. Despite this, the industry exhibits low technical efficiency yet benefits from substantial scale operations. Regression outcomes suggest that company performance is predominantly driven by market power rather than efficiency, with market share significantly enhancing performance, whereas technical and scale efficiencies appear to have minimal impact. The results lend credence to the Harvard School's market power hypothesis.